Pharmacological Optimization Of The Antihypertensive And Vasorelaxant Effects Of A Polyherbal Traditional Chinese Medicine Extract Based On Orthogonal Stimulus-Response Compatibility Approach - Loh, Yean Chun (2017)
Hypertension is one of the major health concerns that are related to various concomitant diseases as well as complications that mainly occur in kidney and cardiovascular system and it has gained the attention of worldwide scientists in recent. Despite the availability of synthetic anti-hypertensive drugs in the market, the low efficacies in monotherapy, as well as adverse effects are frequently being reported. Hence, the current study decided to establish a new antihypertensive formula by applying a new syndromic-disease combination theory of traditional Chinese medicine (TCM). The selection of TCM herbs for current study which includes Gastrodia elata, Uncaria rhynchophylla, Pueraria thomsonii, Panax notoginseng, and Alisma orientale was based on their abilities to treat three main syndromes of hypertension such as fire, phlegm fluid retention, and deficiency syndromes.